2022
DOI: 10.3390/ma15248755
|View full text |Cite
|
Sign up to set email alerts
|

Study on Microstructure and Properties of Black Micro-Arc Oxidation Coating on AZ31 Magnesium Alloy by Orthogonal Experiment

Abstract: The effects of CuSO4 concentration, voltage and treating time on the hemisphere emissivity and corrosion resistance of AZ31B magnesium-alloy black micro-arc oxidation coatings were studied by orthogonal experiment. The microstructure, phase composition, corrosion resistance and hemisphere emissivity of the coating were investigated by scanning electron microscopy, energy-dispersive X-ray spectroscopy, X-ray diffraction, X-ray photoelectron spectroscopy, electrochemical test and infrared emissivity spectrometer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The non-inductive steel tank was used as the cathode in the micro-arc reaction with a circulating cooling system, and the Mg alloy was used as the anode. It has been reported that the anodizing is shortened in this voltage range, the MAO coating grows quickly, and the thickness is uniform [23,24]. A study has shown that when the voltage is less than 450 V, the thickness of the film increases slightly with the increase in voltage; when the voltage is greater than 450 V, the thickness of the film increases significantly with the increase in voltage, and the thickness of the film will greatly affect the corrosion resistance of the alloy; and as the applied voltage rises from 400 V to 500 V, the surface porosity will be relatively stable [25].…”
Section: Methodsmentioning
confidence: 97%
“…The non-inductive steel tank was used as the cathode in the micro-arc reaction with a circulating cooling system, and the Mg alloy was used as the anode. It has been reported that the anodizing is shortened in this voltage range, the MAO coating grows quickly, and the thickness is uniform [23,24]. A study has shown that when the voltage is less than 450 V, the thickness of the film increases slightly with the increase in voltage; when the voltage is greater than 450 V, the thickness of the film increases significantly with the increase in voltage, and the thickness of the film will greatly affect the corrosion resistance of the alloy; and as the applied voltage rises from 400 V to 500 V, the surface porosity will be relatively stable [25].…”
Section: Methodsmentioning
confidence: 97%